“Lean production” as a tool to increase competitiveness of an enterprise - M. K. Ashinova; S. K. Chinazirova; M. P. Khagurova (Новые технологии)
The article considers the concept of “lean production” as a creative trend in the development of modern industrial companies, with the introduction of which firms receive a set of competitive advantages. The system of lean production in companies is focused on the formation of an adaptive and flexible production management system aimed at continuous improvement, as shown by the example of “KAMAZ” PJSC.